Análise de concretos com adição de politereftalato de etileno em situação de incêndio sob influência de tintas intumescentes - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The civil construction industry uses mostly natural materials to carry out its processes, but due to the fact that natural resources are finite, a worldwide concern has been growing for some decades in the search for alternative and viable materials. One of the materials that has been studied in cementitious matrices is Polyethylene terephthalate – PET. This material has been used in scientific studies as a replacement for natural sand for the production of concrete, some studies have shown promising results when PET is used up to certain levels (20%). However, for a new material to have its use validated, it is necessary to verify its behavior and its influence on the properties of the cementitious matrices to which they were inserted against different properties and atypical situations, for example, in the case of a fire. Fire is an event with a high probability of occurrence, and can lead to general deterioration of the damaged structure, depending on its intensity. Having said that, the present work aims to evaluate the mechanical properties of concrete with the partial replacement of natural sand by PET sand, when exposed to high temperatures, simulating an onset of fire. For the experiment, two types of concrete were made, one with traditional aggregates (to be used as a reference mix) and the other, with partial replacement in volume of 20% of natural sand by PET sand. After molding and curing the concrete, part of the samples received physical protection (painting with intumescent paint) and the other part remained in natura (without physical protection). Subsequently, the concretes were exposed to high temperatures (400°C, 600°C, 900°C) and had their mechanical properties evaluated. It was observed that the samples of the reference mix with physical protection showed better mechanical performance compared to samples without protection, when exposed to high temperatures, indicating the efficiency of the physical barrier. For concretes with PET, this behavior was not observed, since the values of axial compression strength reduced for exposures above 400°C, including for concretes with physical protection. It is concluded that for temperatures above 400ºC the physical barrier was not efficient enough to prevent the deterioration of PET in concrete, which ended up resulting in important losses of the mechanical properties of this material. Keywords: Concrete, PET aggregate, fire exposed, intumescent paint, high tempetures.
Keywords: Engenharia civil; Incêndios; Tintas; Civil engineering; Fires; Ink; CNPQ::ENGENHARIAS